Methods for Rapid Protein Depletion in C. elegans using Auxin‐Inducible Degradation. Issue 2 (1st February 2021) - Divekar, Nikita S.; Horton, Hannah E.; Wignall, Sarah M.
Abstract: Numerous methods have been developed in model systems to deplete or inactivate proteins to elucidate their functional roles. In Caenorhabditis elegans, a common method for protein depletion is RNA interference (RNAi), in which mRNA is targeted for degradation. C. elegans is also a powerful genetic organism, amenable to large‐scale genetic screens and CRISPR‐mediated genome editing. However, these approaches largely lead to constitutive inhibition, which can make it difficult to study proteins essential for development or to dissect dynamic cellular processes. Thus, there have been recent efforts to develop methods to rapidly inactivate or deplete proteins to overcome these barriers. One such method that is proving to be exceptionally powerful is auxin‐inducible degradation. In order to apply this approach in C. elegans, a 44–amino acid degron tag is added to the protein of interest, and the Arabidopsis ubiquitin ligase TIR1 is expressed in target tissues. When the plant hormone auxin is added, it mediates an interaction between TIR1 and the degron‐tagged protein of interest, which triggers ubiquitination of the protein and its rapid degradation via the proteasome. Here, we have outlined multiple methods for inducing auxin‐mediated depletion of target proteins in C. elegans, highlighting the versatility and power of this method. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Long‐term auxin‐mediated depletion on plates Support Protocol : Preparation of NGM and NGM‐auxin plates Basic Protocol 2 : Rapid auxin‐mediated depletion via soaking Basic Protocol 3 : Acute auxin‐mediated depletion in isolated embryos Basic Protocol 4 : Assessing auxin‐mediated depletion